PEMANFAATAN RUMPUT LAUT Sargassum sp. DALAM BENTUK PAKAN KONSENTRAT UNTUK MEMPERBAIKI PERTAMBAHAN BERAT BADAN PADA KAMBING - Nurbaya Nurbaya; Khaerani Kiramang; astati astati (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to determine the effect of seaweed Sargassum sp. To weight gain in goats. Concentrate feeding using a different treatment is feed with the addition of Sargassum sp. 10% and 15% and without the addition of Sargassum sp. Research method used Completely Randomized Design (RAL) with 3 treatments and 5 replications ie P0 5 female goat (Control), P1 5 female goat + seaweed Sargassum sp. 10%, P2 5 female goat + seaweed Sargassum sp. 15%. To know the weight gain daily (PBBH). Weighing every 10 days for 2 months. The results showed that average weight gain P0 control 0.014 kg / head / day, P1 (Sargassum sp. 10%) 0.052 kg / day / tail, P2 (Sargassum sp.15%) 0.066 kg/day/The provision of Sargassum sp. had no significant effect on the daily weight gain of female goats, but the graph shows that there is a tendency of daily weight gain of female goats in each treatment